Japan and Korea in the 1990s : - Bridges, Brian (Edward Elgar, 1993)
Japan and Korea in the 1990s examines the historical legacies, the current perceptions and the policy making processes. It then details the recent trends in the economic, political-strategic and cultural dimensions of the relationships. The involvement and influence of the other interested powers, China, the former Soviet Union and the United States, as well as the broader regional context, are considered. A separate chapter concentrates on the current Japan-North Korea negotiations.